Common Framework for Extracting Information and Metrics from Multiple Change Trackers - KENNY, EAMONN (My University, 2012)
An important aspect of EMI is the delivery of ‘quality software’. For this reason the quality assurance (QA) group was introduced. There are a key number of beneficiaries of this work in several work packages. These EMI development and support activities are required to produce key performance indicators (KPIs) and metrics for milestone, quarterly and yearly deliverables based on the information provided by the QA group. However, EMI has a large number of varying sized products, different and existing middlewares and various bug/feature request for change (RfC) trackers used by each product team. The only way to reliably produce KPIs and metrics related to change management in such a varied project is to introduce simplifying, common environments that are readily accessible by all the different customers of the project. For this reason an extensible XML-based framework was defined for storing, plotting, querying and tabulating change tracker information for all its customers
Proceedings of Science
EMI 2nd Technical Conference (EGICF12-EMITC2)
PUBLISHED
Munich, Germany
Keywords: EMI; International Integration; Bug Trackers; Computer Architecture; DATABASE MANAGEMENT; QUALITY ASSURANCE